Sammlung Karl Gerstner. (Bremen : Neues Museum Weserburg Bremen, 1991)
Arman ; Brecht, George ; Christo ; Eggenschwiler, Franz ; Filliou, Robert ; Hains, Raymond ; Hinterreiter, Hans ; Luginbühl, Bernhard ; Roth, Dieter ; Spoerri, Daniel ; Thomkins, André ; Tinguely, Jean ; Weder, Jakob ; von Windheim, Dorothee
Sammlung Karl Gerstner, Neues Museum Weserburg, Bremen, 1991
boek
Keywords: Neues Museum Weserburg, Bremen